SYLVATIC FOCUS OF TRICHINIASIS IN NORTH ESTERN IRAN - I. Mobedi; A.N. Hamidi (Tehran University of Medical Sciences, 1976)
In 1969 and 1976, 830 rodents and carnivores col1ected from North East Iran were examined for Trichinella spiralis. Fifty per cent of golden jackal and 30 percent of red foxes were found infected. The possibility of infection among the rodent was discussed could be considered as new transmission. The results of examination of 1534 total blood samples collected from children up to 15 years old in selected villages of the Hamadan area at, the end of the transmission season of 1973 showed only: serological positive case. This investigation showed that the malaria infection rate, in the selected areas, which seemed to be the most appropriate region in Iran, is now too low for such study.